Software radios for airborne platforms. - Cummings, J.P (IEEE Journal on selected areas in communications)
Defense contributions to the Programmable Modular Communications System (PMCS) Integrated Product Team (IPT) included designs for an RF module based on software radio configurations useful in airborne systems. Several configurations were examined, analyzers were consolidated, and concepts of operation (CONOPS) were evaluated. Geographic separation of platforms and on-board separation of radio modules have consequences for the remote control of reconfigurable radios. This paper identifies organizational roles in software radio development, characterizes the need for software radios in airborne applications, and highlights those configurations found to be attractive. The methodology, CONOPS, and conclusions are summarized